Reactions of sterically congested 1,5-hexadienes: ab initio and DFT calculations on the competition between cope rearrangements and disrotatory cyclobutene ring-opening reactions of bridged syn-tricyclo[4.2.0.02,5]octa-3,7-dienes - Bethke, Sabine; Hrovat, David A.; Borden, Weston Thatcher; Gleiter, Rolf (The journal of organic chemistry, 2004)
The thermolytic behavior of four syn-tricyclo[4.2.0.02,5]octa-3,7-dienes, each spanned by four propano bridges (13, 14, 21, and 26), has been investigated by means of calculations at the UB3LYP/ 6-31G* and CASPT2/6-31G* levels. These calculations predict that 13 should undergo a degenerate Cope rearrangement (EA = 19.6 kcal/mol), whereas the other three C20H24 isomers should prefer a necessarily disrotatory cyclobutene ring-opening reaction. In the case of 14, the ring-opening reaction (EA = 27.2 kcal/mol) is concerted and leads directly to 15, a 4-fold bridged cyclooctatetraene. In the ring opening of 21, the 1,6-bridge in the 4-fold bridged bicyclo[4.2.0]octa-2,4,7-triene 31 prevents formation of the corresponding cyclooctatetraene. In the ring opening of 26, the 4-fold bridged bicyclo[4.2.0]octa-2,4,7-triene derivative 36 is predicted to form the corresponding bridged cyclooctatetraene 38, which should undergo bond shift. The results of these calculations are found to be in very good agreement with the results of experiments on these hydrocarbons.
Gesehen am 28.10.2020